Pemanfaatan Limbah Puntung Rokok sebagai Inhibitor Korosi pada Baja St40 Menggunakan Metode Microwave Assisted Extraction (MAE) di Lingkungan NaCl 3,56%: Utilization of Cigarette Butts Waste as Corrosion Inhibitor on St40 Steel Using Microwave Assisted Extraction (MAE) Method in 3.56% NaCl Environment - Alatif, Ikhsan Akmal; Permatasari, Rahma Puspa; Nurulgina, Rahma; Adzkia, Zahrotul Filza; Andayani, Puri; Putri, Sabrina Aisyah; Adinda; Trirahayu, Dhyna Analyes; Hadiningrum, Kunlestiowati (KOVALEN: Jurnal Riset Kimia, 2024)
Corrosion is a problem that occurs in many industries and causes large losses. The use of corrosion inhibitors is one way to reduce or inhibit corrosion. Cigarette butt waste extract can be utilized as an organic corrosion inhibitor. This study aims to determine the yield of cigarette butt waste extract, the content of cigarette butt waste extract produced using the MAE method qualitatively, determine the optimum conditions for the extraction process with the MAE method based on variations in microwave power of 150 and 300 watts and calculate the efficiency of corrosion inhibitors and the effect of compounds contained in cigarette butt waste extract in 3.56% NaCl environment. The optimum MAE condition was 150 watts and 15 minutes, with an extract yield of 54.38%. Based on the GC-MS test, it is known that cigarette butts waste extract contains alkaloid, terpenoid, and phenol compounds as corrosion inhibitor compounds. Based on corrosion inhibitor testing, the addition of cigarette butt waste extract corrosion inhibitors can suppress or reduce the corrosion rate that occurs on metals with an inhibitor efficiency of 79.19% in non-aerated conditions and 71.53% in aeration with an inhibitor concentration of 1000 ppm in a 3.56% NaCl environment.